(untitled) - FAO (Rome, 1994)
This publication is a complilation of aquaculture production statistics on final harvest reported for fish, crustaceans, molluscs and other aqutic animals, residues anf plants. The following combinations of production statistics are presented: by species and by country; by country and by species; and by species and by enviroment. Values of production expressed in term of US dollars are provided by country, species and species group. Where officially reported national statistics are lacking or are considered unreliable, FAO makes estimates based on the best information available.
Keywords: fisheries